Outcomes associated with the intention of loco-regional therapy prior to living donor liver transplantation for hepatocellular carcinoma - Wu, Tsung-Han (World J Gastrointest Surg, 2020)
BACKGROUND: Loco-regional therapy for hepatocellular carcinoma (HCC) during the period awaiting liver transplantation (LT) appears to be a logical approach to reduce the risk of tumor progression and dropout in the waitlist. Living donor LT (LDLT) offers a flexible timing for transplantation providing timeframe for well preparation of transplantation. AIM: To investigate outcomes in relation to the intention of pre-transplantation loco-regional therapy in LDLT for HCC patients. METHODS: A total of 308 consecutive patients undergoing LDLTs for HCC between August 2004 and December 2018 were retrospectively analyzed. Patients were grouped according to the intention of loco-regional therapy prior to LT, and outcomes of patients were analyzed and compared between groups. RESULTS: Overall, 38 patients (12.3%) were detected with HCC recurrence during the follow-up period after LDLT. Patients who were radiologically beyond the University of California at San Francisco criteria and received loco-regional therapy as down-staging therapy had significant inferior outcomes to other groups for both recurrence-free survival (RFS, P < 0.0005) and overall survival (P = 0.046). Moreover, patients with defined profound tumor necrosis (TN) by loco-regional therapy had a superior RFS (5-year of 93.8%) as compared with others (P = 0.010). CONCLUSION: LDLT features a flexible timely transplantation for patient with HCC. However, the loco-regional therapy prior to LDLT does not seem to provide benefit unless a certain effect in terms of profound TN is noted.